PERGESERAN PARADIGMA HUKUM DARI HUKUM POSITIF MENUJU HUKUM PROGRESIF - . Maryati (Jurnal LEX SPECIALIS, 2010)
Legal knowelegde is a dinamic knowledge that always change, move and waving. If the begining is a law positivism so in history there is rise some a new englightment opinion who has try to correct and repair the assumption in basic criteria law positivism. It show from movement of opinion in historical philosopher, post-posivisme or sosiological jurispudence, so it show the movement in positive law paradigm. This movement from paradigm to the progresive it can be see from the movement of assumption and criteria from the paradigm it self. Law Progresive Paradigm is build by the assumption a) law is created for the human not for himself; b) law is always in status “law in the making” and non final; c) law is a institution of morality and unhearted technology. About the characterism of law progresive is a : a) have agrat goal is a happiness and wealthy of the mankind; b) make a strong sense of morality; c) freedom law not in practically but also theory; d) critical and functional.Key Note : Paradigm of law in progresive law